2013
DOI: 10.1016/j.ridd.2012.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Gaze aversion during social style interactions in autism spectrum disorder and Williams syndrome

Abstract: Publisher's copyright statement: NOTICE: this is the author's version of a work that was accepted for publication in Research in Developmental Disabilities. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reected in this document. Changes may have been made to this work since it was submitted for publication. A denitive version was subsequently published in Research in Developmental Disabilities, 34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…When it came to (non-social) eye gaze toward the background, we found a particularly important interaction between group and topic. Autistic participants showed significantly increased gaze toward the background compared to TD participants across all three topics of conversation, which likely reflects the social and cognitive load of managing the interaction (Doherty-Snedon, Whittle, & Riby, 2013). However, the between-group difference in gaze to the background was reduced in the self-condition relative to the unfamiliar-other condition.…”
Section: Discussionmentioning
confidence: 91%
“…When it came to (non-social) eye gaze toward the background, we found a particularly important interaction between group and topic. Autistic participants showed significantly increased gaze toward the background compared to TD participants across all three topics of conversation, which likely reflects the social and cognitive load of managing the interaction (Doherty-Snedon, Whittle, & Riby, 2013). However, the between-group difference in gaze to the background was reduced in the self-condition relative to the unfamiliar-other condition.…”
Section: Discussionmentioning
confidence: 91%
“…The first requirement was to accommodate an open-loop style of visuomotor control, in which visual feedback is not integrated into the execution of an ongoing movement (Haswell, Izawa, Dowell, Mostofsky, & Shadmehr, 2009). This design goal takes account of the known difficulty of many people with autism in making use of sensory feedback, such that gazing towards the target of a movement confers no advantage and can interfere with cognitive and motor resources necessary for successful communication (Chen, et al, 2012;Doherty-Sneddon, Riby, & Whittle, 2012;Doherty-Sneddon, Whittle, & Riby, 2013). People with autism often fixate only briefly before movement and then avert their gaze.…”
Section: Initial Design Features/requirementsmentioning
confidence: 99%
“…Maintaining appropriate social gaze is a critical prerequisite for language development, emotion recognition, social engagement, and general learning through joint attention [Emery, ; Morales et al, ; Farroni et al, ; Brooks and Meltzoff, ; Csibra and Gergely, ; Itier and Batty, ; Senju and Johnson, ]. For example, several studies have indicated that high levels of social gaze avoidance can negatively impact social interaction skills and communication flow, given that crucial non‐verbal gestures and facial expressions that usually aid social interaction will be missed [Doherty‐Sneddon et al, ; Riby et al, ]. Given these factors, it seems important to examine and quantify social gaze in FXS in a naturalistic social setting (i.e., while individuals are actually engaged in a “real‐life” social interaction).…”
Section: Introductionmentioning
confidence: 99%